2017
DOI: 10.1016/j.resourpol.2017.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Does oil predict gold? A nonparametric causality-in-quantiles approach

Abstract: This paper examines the predictive power of oil price for gold price using the novel nonparametric causality-in-quantiles testing approach. The study uses weekly data over the April 1983-August 2016 period for both the spot and 1-month to 12-month futures markets. The new approach, the causality-in-quantile, allows one to test for causality-in-mean and causality-in-variance when there may be no causality in the first moment but higher order interdependencies may exist. The tests are preferred over the linear G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 60 publications
(17 citation statements)
references
References 49 publications
1
16
0
Order By: Relevance
“…The results reported in Table 2 for examining the causal link between oil and gold prices in spot and futures markets are based on restrictions imposed in a 3 Complete details of the unit root tests are available upon request from the authors. See also Shahbaz et al (2017). 4 Details of the cointegration tests are not reported to preserve space but available from the authors upon request.…”
Section: Data and Empirical Findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…The results reported in Table 2 for examining the causal link between oil and gold prices in spot and futures markets are based on restrictions imposed in a 3 Complete details of the unit root tests are available upon request from the authors. See also Shahbaz et al (2017). 4 Details of the cointegration tests are not reported to preserve space but available from the authors upon request.…”
Section: Data and Empirical Findingsmentioning
confidence: 99%
“…Other studies, including Soytas, Sari, Hammoudeh, and Hacıhasanoglu (), Liao and Chen (), Sari, Hammoudeh, and Ewing (), Hammoudeh and Yuan (), Narayan et al (), Šimáková (), Le and Chang (), and Lee, Huang, and Yang (), however, did not find evidence of the relationship between the movement of the prices of oil and gold. Shahbaz, Balcilar, and Ozdemir (), using a nonparametric causality‐in‐quantiles test, showed that the oil price has weak predictive power for the gold price, and the causality‐in‐variance tests found strong support for the predictive capacity of oil for gold market volatility. According to others, the prices of oil and gold act simultaneously because they are correlated with the movement of their long‐term driving factors, such as volatility in U.S. dollars and the turmoil in the international politics (e.g., Bampinas & Panagiotidis, ; Le & Chang, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Awartani (2013), Ji (2018), Li and Wei (2018), Peng et al (2018), Shahzad (2018), Wang and Wu (2018), Abdullah et al (2016) etc. ), between oil and gold (Le and Chang (2012), Tiwari and Sahadudheen (2015), Shahbaz et al (2017) and Kumar (2017) ), and among oil, gold and stock markets (i.e. Raza et al (2016), Mensi et al (2017b), Lau et al (2017), Bouri et al (2017, Tursoy andFaisal (2018) ) using various kinds of econometric methods.…”
Section: Introductionmentioning
confidence: 99%
“…The outcome revealed weaker contagion effect for emerging markets in Latin America, strong contagion for European and Middle East markets and insignificant long run association after the crisis. Shahbaz et al (2017) explored the predictive power of oil price on gold price through causality in quintiles approach. The findings displayed the evidence of weak predictive power of oil price for forecasting gold price and strong predictive power of oil for volatility of gold market.…”
Section: Literature Reviewmentioning
confidence: 99%